2019
DOI: 10.1021/acs.cgd.9b00463
|View full text |Cite
|
Sign up to set email alerts
|

Photodimerization of a 1D Ladder Polymer through Single-Crystal to Single-Crystal Transformation Has an Effect on Electrical Conductivity

Abstract: A one-dimensional coordination polymer (1D CP), [Cd­(bpe)­(p-brba)2] n (1), has been synthesized by the slow diffusion method keeping the mixture of Cd­(NO3)2·6H2O and 1,2-bis­(4-pyridyl)­ethylene (bpe) ligand along with para-bromobenzoic acid (p-brba) in the dark. Interestingly, the compound 1 undergoes a single-crystal to single-crystal (SCSC) photochemical [2 + 2] cycloaddition reaction to generate dimerized 1D CP [Cd­(rctt-tpcb)1/2(p-brba)2] n (2) [rctt-tpcb = rctt-tetrakis­(4-pyridyl)­cyclobutane]. As a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…Rational design of thermally and chemically stable CPs promotes their electronic applications. The control of electrical conductance by controlling the molecular structure or molecular assembly is a key issue in molecular electronics. Interestingly, our group is able to project a number of CPs for application in electrical conductivity and device fabrication. …”
Section: Introductionmentioning
confidence: 99%
“…Rational design of thermally and chemically stable CPs promotes their electronic applications. The control of electrical conductance by controlling the molecular structure or molecular assembly is a key issue in molecular electronics. Interestingly, our group is able to project a number of CPs for application in electrical conductivity and device fabrication. …”
Section: Introductionmentioning
confidence: 99%
“…Surrounded by the several luminescence-based sensors, coordination polymers (CPs) have emerged as a future generation sensor system for ions because of their stimulating constructions, tunable physical and chemical properties as well as high stability. [17][18][19][20] These hybrid materials have already been ascertained as a fascinating class of molecules owing to their incredible potential for diverse applicability. In particular, fluorescent CPs deliver a number of advantages over conservative fluorophores.…”
Section: Introductionmentioning
confidence: 99%
“…Coordination polymers have recently surfaced as an important class of materials to have conductive properties and find applications in Schottky diodes and photosensing devices. However, fabrication of electronic devices with CPs is still a challenge because they are hybrid materials (composed of organic ligands and inorganic metal ions). , The redox inactive organic ligands have very low conductivity, which results in overall lowering of conductivity of the species. Nevertheless, with the proper selection of the components, CPs can be branded as device applicable materials.…”
Section: Introductionmentioning
confidence: 99%
“…are highly conductive and show interesting photochemical and photophysical properties, presumably due to their flexible nature and ability to produce different molecular geometries with severe distortions. It has been noted that both structural stability and thermodynamic stability make an impact on their electrical properties. Relatively strong covalent bonding among nodes and linkers provides higher stability and increases the effective efficiency in optoelectronic fields. Recently, it has been reported that structural transformations by the photodimerization reaction have significant impacts on the electrical conductivity of the species, but until now, there has been no report on how geometrical isomerism ( cis – trans ) in CPs can affect the electronic properties of the complexes. …”
Section: Introductionmentioning
confidence: 99%